Analisis Anggaran Kas Pada UMKM Kuda Kepang Mas Bagong di Dukuh Wates, Dusun I, Cepogo, Cepogo, Boyolali - Novian Alvina Siri; Rafi Kurniawan; Ardi Febriawan; Jarwono Jarwono; Muhammad Aditya Yulianto (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze cash budget management at the Kuda Kepang Mas Bagong MSME located in Wates Hamlet, Cepogo Village, Boyolali Regency. This MSME focuses on traditional kuda kepang crafts that have economic and cultural value as a support for local performing arts. The method applied is a descriptive qualitative method with data collection techniques through observation and direct interviews with the business owner. The data reviewed includes the production process, production capacity, cost structure, selling price, revenue, and marketing system. The results of the study indicate that the Kuda Kepang Mas Bagong MSME has consistent market demand, especially for medium-sized kuda kepang products. However, production capacity limitations due to the use of one worker are a major obstacle in increasing business turnover. In addition, cash budget management is still carried out in a simple and unorganized manner, so the potential for liquidity control and financial planning has not reached an optimal level. This study concludes that developing a more organized cash budget and increasing production capacity can be a key strategy in improving the financial performance and sustainability of the Kuda Kepang Mas Bagong MSME.